Aplicação da justiça restaurativa: três experiências brasileiras - Zanellato, Fabíola (2018)
The theme of this dissertation is Restorative Justice, which stands out in the contemporary scenario as an alternative to the traditional model of penalty enforcement. Restorative Justice presents itself as a technique of conflict resolution, increasingly accepted and applied within and outside the judicial sphere. Its main principle is to restore the social relations of those involved in litigation, who are invited to participate voluntarily in the so-called restorative circles in which the victim plays a leading role in the restorative process. In the present study, we sought to verify how this technique has been applied by three coordinators of Restorative Justice in Brazil. The coordinators of the Restorative Justice of São Paulo, Brasília and Paraná were interviewed. The three participants answered a questionnaire with comprehensive questions about Restorative Justice, which addressed the criteria adopted by them for choosing the cases that are subjected to this technique, for which crimes they use it and which methods are applied. The present study is important to verify in practice how Restorative Justice has been applied in three Brazilian regions, São Paulo, Brasília and Paraná, highlighting the opinion of the three coordinators about their experiences with this technique. The present dissertation is linked to Forensic Psychology as an area of concentration and research line of the Postgraduate Program in Psychology of the Tuiuti University of Paraná.